Peningkatan Keterampilan Kelompok Masyarakat melalui Pelatihan Budidaya Ikan Nila di Desa Karangtengah, Kabupaten Sukabumi - Donwill Panggabean; Sujono Sujono; Chikita Lestari Sapuriningsih; Rauzatul Nazzla; Rinda Noviyanti; Jan Hotman; Hedi Heryadi; Erina Hertanti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Mustika Rahayu community group is engaged in tilapia cultivation for consumption, located in Karangtengah Village, Cibadak District, Sukabumi Regency. The downturn due to the Covid-19 pandemic is also experienced by this business group, and this condition is getting worse due to low skills on how to cultivate tilapia properly and correctly, the high price of feed and medicines, and the lack of knowledge to do fish farming online. The results of the assistance and training activities for tilapia cultivation skills carried out to partners, namely the Mustika Rahayu fish farming business group, empower them, as evidenced by the following: 1) increased partner knowledge about tilapia cultivation in round ponds with biofloc system/technology; 2) increased knowledge and skills of partners in conducting good tilapia farming; and 3) increased tilapia production by 40% from before the implementation of the activity. This Community Empowerment (PKM) project had a positive impact, especially on partners who were able to cultivate tilapia properly in biofloc ponds.